Enhancing chlamydospore production in Duddingtonia flagrans on solid substrate: The impact of mannitol and varied cultivation conditions - Junco, Milagros (2024)
Duddingtonia flagrans is a nematophagous fungus which has shown promising results as a non-chemical parasitic control tool. The fungus disrupts the parasite´s life cycle by trapping larvae in the environment through the networks generated from chlamydospores, thus preventing the reinfection of animals. One barrier to the development of a commercial product using this tool is the need to increase chlamydospore production in the laboratory for its administration to livestock. The purpose of this study was to evaluate the addition of mannitol to an enriched culture medium and the effect of adverse cultivation conditions on chlamydospore production. D. flagrans was cultivated on Petri dishes with corn agar for 4 weeks at 27 °C and 70% relative humidity (RH). Four groups were then formed, all with Sabouraud agar as a base, to which different growth inducers were added: GSA (glucose Sabouraud agar), GSA-MI (glucose Sabouraud agar + meso inositol), GSA-E (enriched glucose Sabouraud agar), and AE-M (enriched agar + mannitol). After 4 weeks, chlamydospores were recovered by washing the surface of each plate with distilled water and then quantified. The medium that yielded the highest amount of chlamydospores was subjected to different cultivation conditions: NC (normal conditions): 70% RH and 27 °C, AC (adverse conditions) 1: 20% RH and 40 °C, CA2: 60% RH and 27 °C, and CA3: 55% RH and 24 °C. It was determined that mannitol increases chlamydospore production (65x106 chlamydospores/plate), and when reducing humidity by 10% under cultivation conditions it resulted in an approximately 10% increase in chlamydospore production compared to the control group. These results suggest that the addition of polyols, as well as its cultivation under certain environmental conditions, can improve chlamydospore production on a laboratory scale.